Optimization of saccharification prospective from starch of sweet potato roots through acid-enzyme hydrolysis: structural, chemical and elemental profiling - Jagatee, Suman; Priyadarshini, Sonali; Pradhan, Chinmay; Sahoo, Santi L.; Mohanty, Rama C.; Ram, Shidharth S.; Sudarshan, Mathummal; Teka, Tilahun A.; Rout, Jyoti R. (Acta Biologica Szegediensis, 2021)
The sweet potato root, a potent source of starch which is being considered as an efficient alternative for fuel ethanol production in recent times. The starchy substrate needs to be subsequently dextrinized and saccharified so as to enhance the utilization of its carbohydrates for ethanol production. In the present investigation, acid-enzyme process was conducted for the dextrinization and saccharification of sweet potato root flour (SPRF). The best optimized condition for dextrinization was achieved with an incubation period of 60 min, temperature 100 ºC and 1M HCl. However, for saccharification, the best result was obtained with an incubation of 18 h, pH 4, temperature 65 ºC and 1000 U concentration of Palkodex®. After the dextrinization process, maximum concentrations of total sugar and hydroxymethylfurfural (HMF) [380.44 ± 3.17 g/kg and 13.28 ± 0.25 mg/g, respectively] were released. Nevertheless, after saccharification, 658.80 ± 7.83 g/kg of total sugar was obtained which was about 73% more than that of dextrinization. After successful dextrinization and saccharification, the structural, chemical and elemental analysis were investigated using techniques such as scanning electron microscopy (SEM), Fourier-transforms infrared spectroscopy (FTIR) and energy-dispersive X-ray fluorescence spectrophotometer (EDXRF), respectively. Effective hydrolysis was demonstrated in thin layer chromatography (TLC) where the HCl was able to generate monomeric sugar such as glucose and maltose. On the other hand, only glucose is synthesized on the mutual effect of HCl and Palkodex®. The SEM findings indicate that the rough structure of both dextrinized and saccharified sample was gained due to the vigorous effect of both acid and enzyme subsequently. The saccharified SPRF when subjected to fermentation with Saccharomyces cerevisiae and Zymomonas mobilis separately, it was observed that Z. mobilis produced more stretching vibration of –OH than S. cerevisiae, which evidenced the better production of bioethanol. Additionally, evaluation of the influence of S. cerevisiae and Z. mobilis through elemental analysis revealed upsurge in the concentrations of S, Cl, Ca, Mn, Fe and Zn and decline in the concentrations of P, K and Cu in the fermented residue of S. cerevisiae and Z. mobilis, however, Z. mobilis showed little more variation than that of S. cerevisiae.